Effectiveness of the Fiocruz recombinant ChadOx1-nCoV19 against variants of SARS-CoV-2 in the Municipality of Botucatu-SP - Costa Clemens, Sue Ann; Fortaleza, Carlos Magno Castelo Branco; Crowe, Madeleine; Tasca, Karen Ingrid; Spadaro, André Gasparini; Souza-Neto, Jayme Augusto; Grotto, Rejane Maria Tommasini; Sider, Regina; Jimeno, Jose; Verstraeten, Thomas; Clemens, Ralf (Frontiers in Public Health, 2022)
Introduction: As the COVID-19 pandemic progresses, rapidly emerging variants of concern raise fears that currently licensed vaccines may have reduced effectiveness against these new strains. In the municipality of Botucatu, São Paulo State, Brazil, a mass vaccination campaign using ChadOx1-nCoV19 was initiated on 16th of May 2021, targeting people 18-60 years old. Two vaccine doses were offered 12 weeks apart, with the second delivered on 8th of August, 2021. This setting offered a unique opportunity to assess the effectiveness of two ChadOx1-nCoV19 doses in a real-life setting. Materials and Methods: Data on testing, hospitalization, symptoms, demographics, and vaccination were obtained from the Hospital das Clínicas da Faculdade de Medicina de Botucatu. A test-negative study design was employed; whereby the odds of being vaccinated among cases versus controls were calculated to estimate vaccine effectiveness (VE; 1-OR). All individuals aged 18-60 who received a PCR test after the 16th of May and were unvaccinated prior to this date were included in the analysis until the study ended in mid-November 2021. Results: 77,683 citizens of Botucatu aged 18-60 received the first dose, and 74,051 received a second ChadOx1-nCoV19 dose 12 weeks later for a vaccination coverage of 84.2% and 80.2%, respectively. Of 7.958 eligible PCR tests, 2.109 were positive and 5.849 negative. The VE against any symptomatic infection was estimated at 39.2%, 21 days after dose 1, and 74.5%, 14 days after dose 2. There were no COVID-19-related hospitalizations or deaths among the 74,051 fully vaccinated individuals. The VE against severe disease was estimated at 70.8% and 100% after doses 1 and 2, respectively. 90.5% of all lineages sequenced between doses 1 and 2 (16th of May-7th of August) were of the Gamma variant, while 83.0% were of the Delta variant during the second period after dose 2 (8th of August-18th of November). Discussion: This observational study found the effectiveness of ChadOx1-nCoV19 to be 74.5% against COVID-19 disease of any severity, comparable to the efficacy observed in clinical trials (81.3% after dose 2), despite the dominance of the Gamma and Delta VoCs. No COVID-19-related hospitalizations or deaths in fully vaccinated individuals were reported.